The Role of Marketing Strategies in Influencing Consumer Purchasing Behavior: A Study on Bashundhara Food and Beverages Limited in Bangladesh. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The Fast-Moving Consumer Goods (FMCG) industry in Bangladesh has become highly competitive, making effective marketing strategies essential for influencing consumer purchasing behavior. This study examines the role of marketing strategies in shaping consumer buying decisions with special reference to Bashundhara Food and Beverages Limited. The research focuses on key marketing dimensions such as product quality, pricing strategy, promotional activities, and distribution effectiveness. A quantitative research approach was adopted, and primary data were collected from 150 consumers using a structured questionnaire based on a five-point Likert scale. The findings indicate that marketing strategies have a significant and positive impact on consumer purchasing behavior, with product quality and promotional activities emerging as the most influential factors. The study provides practical insights for FMCG companies to develop effective marketing strategies that enhance consumer satisfaction, brand preference, and long-term loyalty in the Bangladeshi market.